Ensino de arte e patrimônio cultural: uma ação educativa em torno da azulejaria luso-brasileira de São Luís do Maranhão - Sousa, Marília Martha França (2020)
The historical center of the city of São Luís do Maranhão has one of the most significant collections of Portuguese tiles in Latin America. This collection, preserves pieces of enamelled pottery resulting from an intercultural exchange between Brazil and Portugal that crossed the overseas. However, part of this reliquary of memory and history is being lost in time, due to several factors, including acts of vandalism on the part of the population itself, which for the most part is unaware of the importance of the collection and due to the public policies of preservation, which end up becoming insufficient regarding the supervision and financial incentives for the maintenance of Brazilian cultural assets. I believe that to preserve it is necessary to know. Thinking about this, this research presents the results of an educational action carried out at Neiva Moreira de Santana, a municipal public school located in the city of São Luís do Maranhão. The practical research was carried out with 7 th grade elementary school classes. The methodology used in the field was action research. The objective of the investigation, as well as the educational action, was focused on the realization of the dialogue between teaching of the visual arts and cultural heritage, focusing on the collection of Luso- Brazilian tiles existing in the Ludovic capital. The aim of this research was to present what methods, resources and strategies were used in the teaching learning process with the participants involved in the research. Since it is necessary to know more and more the practices and mechanisms used by teachers of art in the classroom, as well as the devolution of the apprentices during this process, whose one of the objectives was to sensitize them to the recognition and appreciation of the cultural heritage of your city.